The Influence Of Attraction, Accessibility, Amenity And Ancillary On Tourist Satisfaction At Suwat Waterfall Gianyar, Bali - Jumiati, Kadek Ari; Wisnawa, I Made Bayu; Kartimin, I Wayan (Politeknik Internasional Bali, 2025)
Tourist satisfaction is a critical indicator for sustainable destination development, particularly for emerging natural attractions such as Suwat Waterfall in Gianyar, Bali. This study aims to analyze the influence of attraction, accessibility, amenities, and ancillary services on tourist satisfaction. Using an accidental sampling method, data were collected from 140 visitors through questionnaires, observations, interviews, and documentation. Multiple linear regression analysis revealed that attraction and ancillary services have a significant positive effect on tourist satisfaction, while accessibility and amenities show no significant influence. These findings indicate that the unique natural features of Suwat Waterfall and the supporting services provided strongly shape visitor experiences, whereas infrastructure and comfort facilities require further improvement. This study contributes to tourism research by demonstrating that developing nature based destinations must not only preserve core attractions, but also strengthen service quality to enhance visitor satisfaction and ensure long term competitiveness.